Highly Efficient Antibacterial Polymer Composites Based on Hydrophobic Riboflavin Carbon Polymerized Dots - Marković, Zoran M; Kováčová, Mária; Jeremić, Sanja R; Nagy, Štefan; Milivojević, Dušan D; Kubat, Pavel; Kleinová, Angela; Budimir, Milica D; Mojsin, Marija M; Stevanović, Milena J; Annušová, Adriana; Špitalský, Zdeno; et al. (Nanomaterials (Basel, Switzerland), 2022)
Development of new types of antimicrobial coatings is of utmost importance due to increasing problems with pathogen transmission from various infectious surfaces to human beings. In this study, new types of highly potent antimicrobial polyurethane composite films encapsulated by hydrophobic riboflavin-based carbon polymer dots are presented. Detailed structural, optical, antimicrobial, and cytotoxic investigations of these composites were conducted. Low-power blue light triggered the composites to eradicate Escherichia coli in 30 min, whereas the same effect toward Staphylococcus aureus was reached after 60 min. These composites also show low toxicity against MRC-5 cells. In this way, RF-CPD composites can be used for sterilization of highly touched objects in the healthcare industry.
Keywords: carbon polymerized dots; antibacterial surfaces; polymer composites; riboflavin